2015
DOI: 10.3233/jad-150060
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Visinin-Like Protein-1 in the Pathophysiology of Alzheimer’s Disease

Abstract: Calcium ions are crucial in the process of information transmission and integration in the central nervous system (CNS). These ions participate not only in intracellular mechanisms but also in intercellular processes. The changes in the concentration of Ca2 + ions modulate synaptic transmission, whereas neuronal activity induces calcium ion waves. Disturbed calcium homeostasis is thought to be one of the main features in the pathophysiology of Alzheimer's disease (AD), and AD pathogenesis is closely connected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 108 publications
0
36
0
Order By: Relevance
“…As a neuronal calcium-sensor protein, 5,6 VILIP-1 has been suggested as a marker for neuron injury in brain injury models. 7,34,35 Previous studies indicated that the level of CSF VILIP-1 was associated with the concentrations of CSFtau and P-tau, 6,8,9 supporting its utilization as a neurodegeneration marker. In addition, some studies revealed that CSF VILIP-1 could diagnostically discriminate AD from other dementias.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As a neuronal calcium-sensor protein, 5,6 VILIP-1 has been suggested as a marker for neuron injury in brain injury models. 7,34,35 Previous studies indicated that the level of CSF VILIP-1 was associated with the concentrations of CSFtau and P-tau, 6,8,9 supporting its utilization as a neurodegeneration marker. In addition, some studies revealed that CSF VILIP-1 could diagnostically discriminate AD from other dementias.…”
Section: Discussionmentioning
confidence: 94%
“…As a neuronal calcium-sensor protein, 5,6 visinin-like protein 1 (VILIP-1) has been suggested as a biomarker of neuron injury. 7 Previous studies have shown that cerebrospinal fluid (CSF) VILIP-1 was significantly associated with AD, indicating that VILIP-1 may be a potential biomarker for neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The disorder of calcium homeostasis is considered to be one of the main characteristics of the pathophysiology of AD, and the pathogenesis of AD is closely related to the calcium signaling pathway [ 27 ]. Therefore, VILIP-1, as a neuronal calcium sensor protein, might have a connection to the etiology of AD [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of aggregation, functional levels of VSNL1 are decreased, possibly providing a second mechanism to keep GC inactive besides calcium levels. Furthermore, VSNL1 aggregates are found in amyotrophic lateral sclerosis (ALS)-associated deposits, linking them to neuronal impairment [75][76][77][78][79].…”
Section: Functional Redox-dependent Aggregationmentioning
confidence: 99%